Provision of some ancillary services by microgrid agents - João Tomé Saraiva (2010)
This paper describes part of the research developed by the Power Systems Unit of INESC Porto in the scope of the MoreMicrogrids EU financed project (under the Contract No: PL019864). In this project, and apart from other issues, it was investigated how microgrid agents could participate in a more effective way in electricity markets. In this paper we present models to enable the participation of microgrid agents in the provision of ancillary services, namely reactive power/voltage control, active loss balancing and demand interruption. This participation is accomplished after running the day-ahead market and it corresponds to the activation of a specific market to allocate these services. The implementation of this kind of models can contribute to create a new stream of money to microgrid agents so that they can integrate themselves in a more natural way in power systems, eventually eliminating subsidized tariffs that represent in several countries an increasing amount of the final end user tariffs. Finally, the paper includes a Case Study to illustrate the use of the developed approaches.